Effect of Some Parameters in Pellets Production Used for Fish Feeding - Al-Khshali, M. Sh. M. (The Iraqi Journal of Veterinary Medicine, 2012)
The study dealt with the usual fish feed used in fish farms by changing its moisture content from 500 to 600 ml / kg and using three different hole diameters (2,4,6 mm) in manufacturing the pellets. These two variables were studied concerns the effect on productivity and expansion ratio of the pellets, their density and its settling velocity in water, by using the factorial experiment under Completely Randomized Design (CRD) with three replicates and significant effect tests between treatments under (LSD) test at (0.05).The Results showed that with increase mash of diet moisture content from 500 to 600 ml found significant effect in productivity and it provided maximum productivity (27.99 kg/h) with moisture content 600 ml and it significant effect in settle velocity and was the least settle velocity (7.65 cm / s) at moisture 600 ml and results study not found significant effect in expansion ratio and density for pellets with the changing the product holes diameter from 2 to 4 to 6 mm found significant effect in productivity it up was (38.50 kg / h) at hole diameter 6 mm and also found significant effect in expansion ratio and density and settle velocity for pellets it was up the density (1.092 gm / cm3) and the least expansion ratio (-3.14%) and the least settle velocity (6.18 cm/s) at the holes diameter 2 mm.